2021
DOI: 10.18632/aging.202303
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of CENPF inhibits the progression of lung adenocarcinoma mediated by ERβ2/5 pathway

Abstract: Many studies have reported that estrogen (E2) promotes lung cancer by binding to nuclear estrogen receptors (ER), and altering ER related nuclear protein expressions. With the GEO database analysis, Human centromere protein F (CENPF) is highly expressed in lung adenocarcinoma (LUAD), and the co-expression of CENPF and ERβ was found in the nucleus of LUAD cells through immunofluorescence. We identified the nuclear protein CENPF and explored its relationship with the ER pathway. CENPF and ERβ2/5 were related wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…CENPF expressions have been certified to be related to the prognosis and progression of various cancers, such as bladder, breast, and lung cancers [ 38 40 ]. Compared with noncancerous lung tissue, the expression of CENPF mRNA in LASC tissue was increased in GSE51852, which was similar to recent research [ 41 , 42 ]. According to some researches, hsa-miR-205 is identified as an oncogenic miRNA and related to the progression of many cancers, especially lung squamous cell carcinoma (LUSC).…”
Section: Discussionsupporting
confidence: 89%
“…CENPF expressions have been certified to be related to the prognosis and progression of various cancers, such as bladder, breast, and lung cancers [ 38 40 ]. Compared with noncancerous lung tissue, the expression of CENPF mRNA in LASC tissue was increased in GSE51852, which was similar to recent research [ 41 , 42 ]. According to some researches, hsa-miR-205 is identified as an oncogenic miRNA and related to the progression of many cancers, especially lung squamous cell carcinoma (LUSC).…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, CENPF also promotes breast cancer progression and bone metastasis by activating the AKT/mTOR signaling pathway ( Sun et al, 2019 ). Knockdown of CENPF could inhibit the progression of lung adenocarcinoma by suppressing the ERβ2/5 pathway ( Hexiao et al, 2021 ). KDELC1 , also called POGLUT2 , is a protein O-glucosyltransferase which participates in O-glucose modification and modulates Notch trafficking and signaling ( Takeuchi et al, 2018 ; Mehboob and Lang, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In prostate cancer (PC), CENPF has been reported to be a critical regulator of PC metabolism (Shahid et al, 2019). Also, knockdown of CENPF can inhibit the progression of lung adenocarcinoma by suppressing the expression of ER2/5 of the ERβ2/5 pathway (Hexiao et al, 2021). However, the mechanism of how CENPF acts in DLBCL is not yet clear; thus, we performed quantitative proteomic profiling of the CENPF-upregulated DLBCL cell line (generated by adenoviral transfection) and found that the expression levels of various proteins in the DLBCL cell line were also markedly changed, and these proteins were mainly focused on cellular processes, biological regulation, immune system processes and transcriptional regulator activity by GO and KEGG analysis.…”
Section: Discussionmentioning
confidence: 99%